Cultivations of Vibrio cholerae using probing control of glucose feeding - de Maré, Lena; Andersson, Lena; Hagander, Per ([Host publication title missing], 2002)
One reason for cultvating Vibrio cholera is for production of CTB, which is a component in a cholera vaccine. Techniques of high cell density fermentation developed for recombinant E. coli are investigated.In the literature there is evidence of acetate formation when cultivating V. cholerae, and it is probable that the acetate has the same negative consequences for V. cholerae as for E. coli. Formation of acetate in E. coli cultures occurs under anaerobic conditions, but also under fully aerobic conditions in situations with excess carbon source.Mats Åkesson has developed a probing feeding strategy, which avoid overflow metabolism while maintaining a high growth rate. The probing feeding strategy consists of pulses that are superimposed to the glucose feed. The pulses give rise to changes in the glucose uptake, which can be seen in the dissolved oxygen measurements. A feedback algorithm uses the information from the pulse responses to change the feed rate. A safety net decreases the feed rate when maximal stirrer speed is reached to avoid oxygen limitations. The probing feeding has been tested in five fed - batch cultivations with V. cholerae JS1596 in defined media. The strategy is working as well for V. cholerae as for E. coli in minimizing the amount acetic acid formed and avoiding anaerobic conditions. Two hours after the feed start most of the acetic acid accumulated during the batch phase is consumed. During this acetic acid consumption period the resulting growth rate is a bit lower than later on when the acetic acid is depleted. The probing feeding strategy thus gives favorable cultivation conditions in a controlled way.